The vulva dialogues: The sexual-bodily experience of cisgender women - Quintão, A. M. P. (Proceedings of the 7th International Conference on Gender Research, 2024)
Sexuality is an essential part of our lives. Despite being personal, it is deeply impacted by our culture and social scripts. Thus, the sexual-bodily experience of the cisgender woman relates to her life experiences through her body. Nonetheless, the female body is often subjected to prejudice, stigma, and misconceptions, driving women into genital alienation. There is plenty of misinformation on the vulva and the clitoris, even within the scientific community, which not only contributes to many women’s unawareness of their own bodies, but also puts their health at risk in the hands of poorly trained surgeons. Furthermore, the sexual-bodily experience of the cisgender woman is commonly observed from a phallocentric perspective, which tends to override and neglect her agency. My research seeks to analyse the most relevant aspects of the sexual-bodily experience of Portuguese cisgender women who date mostly men, focusing on their relationship with their vulva, their clitoris, and their sexual pleasure. I also want to identify the role of medicine and health professionals in that relationship, within the Western medicine perspective of the female body. The fieldwork is being carried out by qualitative methods, divided into three parts: 1) a minimum of 15 semi-structured, in-depth interviews with health professionals (gynaecologists, gynaecological surgeons, and sex therapists) working in the Lisbon Metropolitan Area (LMA); 2) a minimum of 15 in-depth interviews via the Biographic-Narrative Interpretative Method (BNIM) with Portuguese cisgender women residing in the LMA who date mostly men; and 3) a review of how female genitalia are portrayed in anatomy books used in Portugal’s top medical schools. Therefore, I aim to understand how centuries of control over the female body and decades of medicalization of female sexuality have impacted the corporeality and sexuality of Portuguese cisgender women, to contribute to an in-depth debate on such matters in Sociology.